BRIDGING THE GAP: STRUCTURED AND SUSTAINABLE MENTORSHIP MODELS FOR ENHANCING PARTICIPANT PERFORMANCE IN COMPETITION ENVIRONMENTS - Fitri Afrina; Yusuf Iskandar; H. Kurniawan; Hesri Mintawati (RADJA PUBLIKA, 2026)
This study was conducted to examine structured and sustainable mentorship models in enhancing participant performance within competitive environments. Competitive environments are no longer merely understood as arenas to achieve victory, but also as learning platforms that demand participants possess critical thinking skills, strategy, teamwork, communication, adaptability, and mental readiness. This research employs a systematic literature review method on 10 peer-reviewed journal articles published during the 2016–2026 period. The analysed literature focuses on mentorship, structured mentorship, sustainable mentorship, participant performance, and competitive environments. The findings indicate that relevant mentorship models in competitive environments include technology-enabled mentorship, case competition mentorship, near-peer mentorship, student-led mentorship, structuredcompetence-based mentorship, business plan competition mentorship, as well as project- and team-based mentoring. The findings also reveal that mentorship implementation still faces challenges such as time constraints, mentor-mentee mismatch, weak program structures, digital communication barriers, and suboptimal monitoring and evaluation. This study concludes that sustainable mentorship needs to be designed through clear objectives, precise mentor-mentee matching, structured mentoring agendas,technology utilization, performance evaluation, and post-competition reflection. Thus, mentorship not only supports the achievement of competitive outcomes but also strengthens participants' capacity, autonomy, and long-term learning